Investigating the igneous petrogenesis of Martian volcanic rocks using augite quantitative textural analysis of the Yamato nakhlites. (11th December 2022) - Griffin, Sammy; Udry, Arya; Daly, Luke; Forman, Lucy Victoria; Lee, Martin R.; Cohen, Benjamin E.
Abstract: To better understand volcanism on planetary bodies other than the Earth, the quantification of physical processes is needed. Here, the petrogenesis of the achondrite Martian Yamato (Y) nakhlites (Y 000593, Y 000749, and Y 000802) is reinvestigated via quantitative analysis of augite (high‐Ca clinopyroxene) phenocrysts: crystal size distribution (CSD), spatial distribution patterns (SDP), and electron backscatter diffraction (EBSD). Results from CSD and EBSD quantitative data sets show augite to have continuous uninterrupted growth resulting in calculated minimum magma chamber residence times of either 88–117 ± 6 yr or 9–12 yr. All samples exhibit low‐intensity S‐LS type crystallographic preferred orientation. Directional strain is observed across all samples with intracrystalline misorientation patterns indicative of (100)[001]:(001)[100] (Y 000593 and Y 000802) and {110}<001>or {110} 1 /2 <110> (Y 000749) slip systems. SDP results indicate phenocryst‐bearing crystal‐clustered rock signatures. Combined findings from this work show that the Yamato nakhlites formed on Mars as individual low‐viscosity lava flows or sills. This study shows that through combining these different quantitative techniques over multiple samples, one can more effectively compare and interpret resulting data to gain a more robust, geologically contextualized petrogenetic understanding of the rock suite being studied. The techniques used in this study should be equally applicable to igneous achondrites from other parent bodies.